Inter-Firm Coopetition and Credit Ratings: How the Debt Market Reacts to Inter-Firm Coopetition - Cara Droege; Andrea Greven; Denise Fischer-Kreer; Malte Brettel (British Journal of Management, 2022)
Due to the high importance and severe consequences of credit ratings, we investigate the effect inter-firm coopetition—simultaneous cooperation and competition—has on credit ratings. So far, coopetition research has disregarded its effect on the debt market and research on credit ratings has not considered this evermore occurring mode of alliance. Given the combination of debtholders' high risk sensitivity and coopetition's paradoxical characteristics entailing high risks and potentially high returns, we hypothesize: First, firms who engage in coopetition enjoy higher credit ratings in general. Second, nevertheless, coopetition increases the likeliness of a credit rating downgrade in the short term. Third, firms can weaken the initial, negative reaction through partner selection. Empirical testing with a large-scale, cross-industry sample containing 2569 public firms over a time span of 20 years supports our first two hypotheses. A deeper analysis also validates our third hypothesis. Our research contributes to both literature streams by building on paradox theory and thereby revealing a dark side of coopetition.
Keywords: 650